Alterations in serum proteins and immunoglobulins in diarrhoeic buffalo calves - JOSHI, V B; SAINI, S S; SODHI, S S (The Indian Journal of Animal Sciences, 2013)
Diarrhoeic buffalo calves (14) of 1-2 weeks of age had lower serum protein, IgG and IgM cuucentrations on the first day of onset of diarrhoea than the non-diarrhoeic apparently healthy calves (23). Calves recovered from diarrhoea within 10 days after treatment with phthalyl sulphathiazole, pectin and kaolin, and had significantly lower (P<0.05) levels of IgG but higher levels of IgM. The mean IgM concentration of calves died of colisepticaemia was significantly lower than the diarrhoeic but surviving calves. Treatment of severely diarrhoeic calves (6) with intravenous infusion-of IgM. fraction produced mild anaphylactic shock but resulted in immediate rise in serum IgM levels. The haemoglobin concentration of all diarrhoeic calves was significantly higher (P<0.05) than the non-diarrhoeic calves.